Constitutional Law Reform: Analysis and Impact - Muharuddin; Sokhib Naim; Saharuddin; Sopian; Jusuf Luturmas (Warmadewa Press, 2024)
This research aims to assess the efficacy of the amendments to the 1945 Constitution of the Unitary State of the Republic of Indonesia in promoting democratic values and enhancing government accountability. Utilizing a normative research method, the study involves comprehensive literature reviews and detailed analyses of legal documents, including related laws, regulations, official documents, academic publications, and specific amendments to the Constitution. These amendments, which included limiting the presidential term, increasing the transparency of the general election process, and strengthening the roles of the People's Representative Council and the Regional Representative Council, were evaluated for their impact. The findings indicate that while the constitutional changes have fostered increased accountability and transparency within the government, challenges such as bureaucratic inertia, public ignorance of legal frameworks, and persistent corruption continue to impede full realization of the reforms. The study suggests that enhanced public engagement, stricter law enforcement, and further bureaucratic reform are necessary to overcome these obstacles. Successfully addressing these challenges could lead to a smoother functioning of governance, improved administration, and the establishment of a democratic and just legal state that aligns with Indonesia's aspirations. The potential implications of these reforms are significant, promising to enhance the democratic fabric and accountability mechanisms of the country.